(untitled) (Global Journal of Science Frontier Research, 2017)
Assessment of length-weight relationship and condition factor of a commercially important mollusc species, Periwinkle, Tympanotonus fuscatus, from Okrika estuary was conducted from October, 2015 to February, 2016. A total of 120 samples of the species were hand-picked from the mangrove ecosystem of Okrika. The results obtained showed that the gastropod species had negative allometric growth patterns with a growth exponent, b value of 2.18. This value was confirmed as negative allometric, because it was significantly different (p